2020
DOI: 10.25134/ieflj.v6i2.3383
|View full text |Cite
|
Sign up to set email alerts
|

Padlet for English Speaking Activity: A Case Study of Pros and Cons on Ict

Abstract: As Millennial generation, students nowadays have limitless concept of time and space, they broke logical and physical barriers during the process of communication including in the process of learning. Blanded learning and hybrid learning are one of the latest phenomenon in Education. In shortest perception students will encoder positive effect toward the uses of technology in school but in fact some of them also encounter obstacle and problems. This research aims to project the students� pros and cons on the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
1
10
0
2
Order By: Relevance
“…The last three questions indicated that students felt highly motivated in the course and showed positive attitude towards the use of Padlet and Zoom's breakout rooms. This finding coincides with a few research studies on the aspect that Padlet is a useful and interesting tool, keeping students engaged and motivated in ELT classrooms (Toti & Abahhussain, 2018;England, 2017;Syahrizal & Rahayu, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The last three questions indicated that students felt highly motivated in the course and showed positive attitude towards the use of Padlet and Zoom's breakout rooms. This finding coincides with a few research studies on the aspect that Padlet is a useful and interesting tool, keeping students engaged and motivated in ELT classrooms (Toti & Abahhussain, 2018;England, 2017;Syahrizal & Rahayu, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Turning to the use of Padlet, a survey involving 61 university students reveal positive feedback toward the use of interactive Padlet in the teaching learning process (Setiawati, 2020). Syahrizal and Rahayu (2020) interviewed 35 first-year students at one of the private universities in Cimahi after allowing them the chance to experience Padlet. The findings revealed three main benefits including high level of collaboration with peers and teachers, flexibility in use and tool to set personal goals.…”
Section: Introductionmentioning
confidence: 99%
“…Padlet is an online learning application that is simply often called an online whiteboard or commonly known as an online synchronous platform, Padlet can be used on smartphones, tablets, laptops or computers. Through the Padlet application, it can provide a forum for collaborative learning media between teachers and students in participating simultaneously, both of them can send and share ideas and thoughts in the form of videos, images or writing [32]. Padlet is a free social networking site where people can debate or discuss specific topics and easily use multimedia elements to perfect their words.…”
Section: Padletmentioning
confidence: 99%
“…패들렛은 비어있는 판(blank slate)이기 때문에 사용자가 원하는 콘텐츠로 판을 구성할 수 있고 다른 사람을 초청해서 협업할 수 있다는 특징이 있으며 상호작용할 수 있는 공간이 어떠한 기기로든 어떠한 웹 브라우저든 쉽게 접근할 수 있고 이용하기도 쉽기 때문에 교사와 학생들 모두에게 유용한 교육용 도구가 될 수 있다 (Edward, 2020). 따라서 초기 기존의 많은 연구들은 협업 활동을 지원하기 위한 패들렛의 유용성에 집중된 바 있다 (Beltrán-Martín, 2019;Dembo & Bellow, 2013;Ellis, 2015;Fuchs, 2014;Megat, Yusoff, Azmi, Shariff, & Hassan, 2020;Rashid, Yunus, & Wahi, 2019;Saetra, 2021;Zhi & Su, 2016) (Diab, 2019;Lestari, 2017;Taufikurohman, 2018) 최근에는 말하기 학습까지 (Syahrizal & Rahayu, 2020) Gramma Tala: But in time, some began to seek Te Fiti's heart…. They believed if they could possess it, the great power of creation would be theirs.…”
unclassified